Retirement Planning for Dummies - Krantz, Matthew (For Dummies [Imprint], 2020)
Advice and guidance on planning for retirement Retirement Planning For Dummies is a one-stop resource to get up to speed on the critical steps needed to ensure you spend your golden years living in the lap of luxury-or at least in the comfort of your own home. When attempting to plan for retirement, web searching alone can cause you more headaches than answers, leaving many to feel overwhelmed and defeated. This book takes the guesswork out of the subject and guides readers while they plan the largest financial obligation of their life. Take stock of your finances Proactively plan for your financial future Seek the help of professionals or go it alone Use online tools to make retirement planning easier Whether you're just starting out with a 401(k) or you're a seasoned vet with retirement in your near future, this book helps younger and older generations alike how to plan their retirement.
Keywords: Finance, Personal; Investments; Retirement income -- Planning; Retirement -- Planning; Investissements; Revenu de retraite; Planification; Retraite; Planification; portfolios (financial records); Retirement income; Planning; Retirement; Planning